The effect of deployment and optimal dispatch of shared electric shuttles on the energy efficiency of campus transit - Robert Smith; Ardalan Vahidi (Public Transport, 2026)
Abstract A problem that public transit systems are facing is low energy efficiency and the continued cycling of large transport vehicles at low occupancy when low demand for transport exists, wasting energy. To remedy this issue, we propose a hybrid system of existing diesel buses and automated electric shuttles to augment the system during off-peak hours. Due to their higher occupancy rates and more efficient powertrains, these shuttles could reduce the system energy used per traveled passenger mile. Automated electric shuttles can reduce the energy use of the public transit system further while still meeting ridership demands during low-demand times using optimized routes. These shuttles are considered on-demand. We will formulate and solve an optimization algorithm to optimally allocate the shuttles to requests based on predicted fuel use, predicted time cost, and the number of missed requests. By using traffic microsimulation software, the shuttles can travel along their optimized routes while being affected by transient traffic conditions. This method gives a better approximation of their real-world energy use. The microsimulation demonstrates that systems where buses operate during times of high demand and automated electric shuttles operate during times of low demand have lower energy use per traveled passenger mile and no missed requests. This hybrid system improves the energy used per traveled passenger mile by at least 32% when compared to the current system of buses. The hybrid system reduces both energy use and traveled passenger mile. The hybrid system also improves the total energy use by at least 64% compared to the current bus system.